2016
DOI: 10.1021/acssuschemeng.5b01620
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Cellulose Nanocrystals with a High Yield of 88% by Simultaneous Mechanochemical Activation and Phosphotungstic Acid Hydrolysis

Abstract: An efficient approach for extracting cellulose nanocrystals (CNCs) was put forward through phosphotungstic acid (PTA) hydrolysis of cellulose raw materials under mechanochemical activation. Response surface methodology was employed for experimental design to determine the optimum conditions of CNCs preparation with software Design Expert. The results showed that quadratic polynomial model was qualified to represent the relationship between the response and independent variables and the regression model defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(99 citation statements)
references
References 34 publications
1
98
0
Order By: Relevance
“…On the other hand, the unsulfated crystals tend to collapse at higher decomposition temperature [53];…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the unsulfated crystals tend to collapse at higher decomposition temperature [53];…”
Section: Resultsmentioning
confidence: 99%
“…where I 002 and I amp are the intensities of diffraction peaks at 2Ξ = 22–23° and 15–17°, respectively …”
Section: Methodsmentioning
confidence: 99%
“…Because this method is a solid/liquid/solid three-phase reaction, the reaction efficiency is low and the reaction time is relatively long compared with the mineral acid hydrolysis method. Further research results showed that the reaction time was significantly shortened under the optimal conditions, and the obtained CNCs had a high crystallinity index (79.6%) with a 84% yield [78]. Torlopov et al also reported a CNCs preparation process using phosphotungstic acid/acetic acid system to destruct cotton cellulose [79].…”
Section: Solid Acid Hydrolysismentioning
confidence: 99%